Case Report: Anlotinib Reverses Nivolumab Resistance in Advanced Primary Pulmonary Lymphoepithelioma-Like Carcinoma With FGFR3 Gene Amplification - Liu, Yanyang; Long, Lang; Liu, Jiewei; Zhu, Lingling; Luo, Feng (Frontiers in Oncology, 2021)
Background Primary pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare type of non-small cell lung cancer (NSCLC). Currently, anti-programmed death-1 (PD-1)/programmed death ligand-1 (PD-L1) has become an important treatment for NSCLC. Anti-human PD-1 monoclonal antibodies, such as nivolumab, significantly prolong the survival time of patients with advanced lung adenocarcinoma and lung squamous cell carcinoma. However, there are few reports on the therapeutic effect, drug resistance mechanism, and strategies to overcome resistance to anti-PD-1/PD-L1 treatment in advanced pulmonary LELC. We report the case of a patient with advanced pulmonary LELC harboring fibroblast growth factor receptor (FGFR)3 gene amplification that showed resistance to nivolumab. After treatment with anlotinib, a multi-targeted small-molecule tyrosine kinase inhibitor, the patient’s resistance to nivolumab was reversed. She achieved long-term disease remission with a combination of anlotinib and nivolumab treatment. Case Presentation A 68-year-old woman was diagnosed with stage IVA pulmonary LELC. After multiple-line chemotherapy, her disease progressed. Since the PD-L1 expression rate of the patient was 90%, nivolumab was administered. However, the therapeutic effect of nivolumab was not ideal; the disease continued to progress, and a new cervical lymph node metastasis appeared. FGFR3 gene amplification was detected in lymph node metastasis. Based on this gene abnormality, we added anlotinib to the treatment. After two cycles of anlotinib and nivolumab, the metastatic focus of the patient was significantly reduced. The patient continued to receive this combined treatment and achieved remission for more than 15 months. Conclusion Pulmonary LELC with FGFR3 gene amplification may not respond well to nivolumab monotherapy. The combination of anlotinib and nivolumab can reverse the resistance to nivolumab in pulmonary LELC with FGFR3 gene amplification.